Comparison of fatty acid profiles between successful and usual aging elderly - Nabilah Rosney,; Hasnah Haron,; Maihiza Salleh,; Suzana Shahar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Increased the consumption of polyunsaturated (PUFA) and omega-3 fatty acid may be one of the strategies to prevent morbidity and mortality among elderly. This study aimed to identify the plasma fatty acid profile and intake among older adults who aged successfully (SA) as compared to the usual agers (UA). This cross-sectional comparative study was conducted among 48 SA (mean age 66.4+4.7 years old) and 42 UA (mean age 68.4+4.8 years old). The plasma fatty acid profile was determined using gas chromatography. Fatty acid intake was measured by using the validated Fatty Acid Omega-3 intake food frequency questionnaire. The percentage of saturated fatty acids (SFA) in blood plasma of UA (men 62.2+6.4%, women 62.9+7.0%) were significantly higher (p<0.05) compared to SA (men 53.7+15.8%, women 57.1+9.5%). On the other hand, the percentage of monounsaturated (MUFA), polyunsaturated (PUFA) omega-3 and omega-6 fatty acids were the opposites. Fatty acids intake among SA was higher compared to UA. SFA (SA=5.0+2.5%, UA=4.6+2.9%) and total omega-3 (SA=0.5+0.4%, UA=0.4+0.3%) intakes met the recommended nutrient intake (RNI). However, mean intakes of MUFA (SA=5.3+2.4%, UA=4.7+2.7%) and linoleic acid (LA) (SA=0.5+0.7%, UA=0.3+0.5%) were below than the RNI. Percentages of subjects who did not meet the RNI for omega-3 and MUFA were 44.2% and 97.7% for SA and 47.4% and 95% for UA, respectively. SA had a higher level of plasma PUFA and MUFA, but lower in SFA when compared to UA. MUFA and LA were more likely to be inadequate in the diet of older adults, particularly the UA.